Project Analysis: A Research Gap - Sorooshian, Shahryar; Ismail, MD Yusof; Ibrahim, Abdullah; M D, Arifpin; Siali, Fadilah (Journal of Management and Science, 2013)
This Paper is a short communication in the form of a research proposal to highlight the gap of research in project management area. This study focuses on construction projects and suggests research objectives for further studies, with a research roadmap for younger researchers